2005
DOI: 10.1200/jco.2005.11.981
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Study of Low-Dose Decitabine in Patients With Chronic Myelogenous Leukemia Resistant to Imatinib Mesylate

Abstract: Decitabine induces hypomethylation and has clinical activity in imatinib refractory chronic myelogenous leukemia. We hypothesize that the inverse correlation between hypomethylation 2 weeks after therapy and response is due to a cell death mechanism of response, whereby resistant cells can withstand more hypomethylation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
193
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 284 publications
(201 citation statements)
references
References 23 publications
8
193
0
Order By: Relevance
“…Both drugs are particularly effective when administered at low doses, which are sometimes below 10% of their maximum tolerated doses (Issa and Kantarjian, 2009). These conditions are generally assumed to maximize DNA demethylation responses, and several studies have confirmed that drug-induced DNA demethylation occurs in patients (Issa et al, 2005;Mund et al, 2005;Soriano et al, 2007;Stresemann and Lyko, 2008). However, a direct link between DNA demethylation and clinical responses has not been demonstrated yet and there are currently no established DNA methylation biomarkers that accurately predict patient responses (Fandy et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Both drugs are particularly effective when administered at low doses, which are sometimes below 10% of their maximum tolerated doses (Issa and Kantarjian, 2009). These conditions are generally assumed to maximize DNA demethylation responses, and several studies have confirmed that drug-induced DNA demethylation occurs in patients (Issa et al, 2005;Mund et al, 2005;Soriano et al, 2007;Stresemann and Lyko, 2008). However, a direct link between DNA demethylation and clinical responses has not been demonstrated yet and there are currently no established DNA methylation biomarkers that accurately predict patient responses (Fandy et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, 5-aza-2 0 -deoxycitidine has been shown to have clinical activity in imatinib resitant CML. 27 The role of Hck inactivation in imatinib resistance therefore needs further studies.…”
Section: Discussionmentioning
confidence: 99%
“…No reports described hypermethylation of any of the STAT regulators in CML. However, in line with the promising results following treatment with decitabine in patients with imatinib-resistant disease [77], it may be justified to further study the genes to be hypomethylated.…”
Section: Hypermethylation Of Stat Inhibitors In Chronic Leukemiasmentioning
confidence: 99%